Quality evaluation of Slovak universities in terms of internationally recognized rankings - Belkovicsová, Daša; Repková, Denisa (Ocena jakości słowackich uniwersytetów w kontekście uznanych międzynarodowych rankingów, 2011)
A new challenge for individual countries has become a phenomenon of building a knowledge-based society, where higher education institutions represent a decisive determinant. It is therefore necessary to ensure their adaptation to the requirements of a knowledge-based society. The main intention and strategic aim of every country should, therefore, be to ensure the access to qualitative higher education with international standards. Higher educational institutions must be regarded as high quality ones not only in their countries, but also abroad. This requires obtaining internationally recognized quality. The evaluation of quality of educational institutions is made at the country level, as well as from an international perspective
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 221, s. 48-54